Molecular-scale characterisation of humic substances using isotope-filtered nD NMR spectroscopy - Bell, Nicholle Georgina Anneke (The University of Edinburgh, 2016)
Humic substances (HS), the complex mixture of organic molecules produced by microbial and abiotic degradation of plant and animals residues, are the major components of organic matter in soil and natural waters. As such, they are vital to the integrity of soil, play important roles in nutrient biogeochemical cycling and determine the mobility and fate of both nutrients and contaminants. How HS enact their varied roles, however, is largely unknown due to the lack of comprehension of their molecular make-up. What is known is that they contain aromatic (e.g. phenols, condensed aromatics) and aliphatic (e.g. carbohydrates, lipids) molecules with prevailing carboxyl and hydroxyl functionalities. As for other complex chromatographically inseparable mixtures, high-resolution analytical techniques such as Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (FT-ICR MS) as well as Nuclear Magnetic Resonance (NMR) spectroscopy have been applied to study HS composition at the molecular level. While FT-ICR MS can provide molecular formulae, it is only NMR that can unveil structures. Until now, however, very few unambiguous structures of individual molecules have emerged from standard NMR experiments. This is because purposely designed multidimensional NMR experiments are required to achieve ‘spectroscopic separation’ where chromatography fails. In this work, ‘spectroscopic separation’ was accomplished with the aid of chemical modification in the form of 13C methylation of COOH and OH groups. 13C containing tags allow the observation of signals only from molecules carrying these tags. In combination with purposelydesigned isotope-filtered NMR experiments, these tags act as spies reporting on their surrounding structure. This is achieved by utilising scalar and dipolar couplings to transfer the polarisation between protons and carbons of the 13CH3O groups and nuclei of the parent molecules. The necessary spectral resolution is attained using 3D/4D NMR experiments. This approach provides access to an array of correlated chemical shifts of HS molecules and represents a paradigm shift in the use of tags in investigations of complex mixtures: instead of focusing only on the tags, they are used to obtain structural information from the molecules they are attached to. The compounds at the centre of this investigation are the phenols of HS. These molecules are thought to be important in many of the key processes in organic matter rich soils, particularly peat. For example, their accumulation is thought to impair the activity of extracellular enzymes essential for the degradation of peat HS. Understanding the nature and source of phenols would provide a more fundamental framework for rationalising their role in peat, as well as other carbon rich soils. The developed methodology was initially tested on model mixtures containing 3 or 9 phenolic compounds before applying it to a operational fraction of HS, fulvic acid, extracted from a Scottish raised peat bog. For this fulvic acid, over 30 major phenolic molecules/moieties were identified, many of which can be directly traced to the flora prevalent in the vicinity of the sampling site. For the first time in 150 years of HS research, a novel analytical methodology has yielded unambiguous structural information, providing the first steps towards understanding the various roles of HS in natural systems.
Keywords: peat; FT-ICR MS; NMR; spectroscopic separation; organic matter rich soils; phenolic molecules